Genome Sequences of a Novel Vietnamese Bat Bunyavirus - Oude Munnink, B; Phan, M; van der Hoek, L; Kellam, P; Cotten, M; the VIZIONS Consortium (American Society for Microbiology, 2016)
© 2016 Oude Munnink et al. To document the viral zoonotic risks in Vietnam, fecal samples were systematically collected from a number of mammals in southern Vietnam and subjected to agnostic deep sequencing. We describe here novel Vietnamese bunyavirus sequences detected in bat feces. The complete L and S segments from 14 viruses were determined.